Analisis Trik dan Teknik Marketing Generasi Z dalam Mempromosikan Produk Somethinc di Instagram - Putriana, Rahmi; Kholil, Syukur (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
As the digital world develops rapidly, marketing dynamics also change, requiring constant strategy adaptation on the part of marketers. The emergence of Generation Z as a new economic force in the digital marketing era is one of the most significant developments in the last ten years. So, on this occasion the researcher wants to research the tricks and techniques of Generation Z in promoting a product to make the current digital marketing industry develop, this research is a case study conducted on generation Z influencers in carrying out tricks and techniques in promoting somethinc products. The research method used is qualitative with a phenomenological approach, which allows researchers to understand individual or group behavior and related social phenomena. The research results revealed that Generation Z's use of influencer marketing techniques succeeded in attracting consumer attention and contributed to increasing sales of Somehinc products. This research also shows that Generation Z marketing techniques, especially through Instagram social media, have a significant impact on product marketing.